Cu sil Denture for Rehabilitation of Ectodermal Dysplasia - Maharjan, S; Basnet, BB; Parajuli, PK; Suwal, P; Luitel, A (Journal of Nepalese Prosthodontic Society, 2023)
Ectodermal dysplasia (ED) is an inherited disorder of ectoderm that results in aberrant development of tissues of ectodermal origin, namely skin, hair, nail, eccrine glands, and teeth. They present with missing teeth, sparse scalp hair, hyperpyrexia related to intolerance to heat.Patients suffering from ED can lead normal life as it does not affect intelligence. But being bald and edentulous at any stage of life lowers the confidence of a person. Young children and adolescents go through the harsher scenario.As this disorder manifests in infancy, prosthetic rehabilitation for missing and crooked teeth not only helps in, mastication, speech articulation, social acceptance and self-confidence.This case report includes prosthetic rehabilitation of a 16-years-old male with ectodermal dysplasia with a complete denture on the lower arch and cu sil denture on the upper arch.